Role of Patients and Parents in Pediatric Drug Development. (September 2019) - Tsang, Vivian W. L.; West, Leanne; Woods, Christine; Koh, Chester J.; McCune, Susan; Mullin, Theresa; Smith, Sharon R.; Gaillard, Segolene; Claverol, Joana; Nafria, Begonya; Preston, Jennifer; Dicks, Pamela; et al.
Patient engagement in health care has been an emerging priority in the global effort and move toward the consideration of patients as experts of their own conditions. However, the input of pediatric patients and their families have not been consistently requested nor regarded as valuable when deriving protocols for, as well as assessing the outcomes of, pediatric clinical trials. Extending this mutual collaboration further upstream is important, especially in the area of pediatric drug development where the lack of formalized trials for children and adolescents result in the increased use of off-label prescribing and risk of adverse effects. While recent changes to European and North American legislation contributed to the inclusion of children and youth in pediatric drug development, the lack of systematic guidelines and methodologies in literature serve as barriers for practical application. When combined with the work of external pediatric advocacy and patient advisory groups, the hope is that pediatric patient voices can be brought forward for the future. This article brings together international experts to review current best practices, progress from regulatory agencies, as well as global advocacy efforts to involve patients and families in the pursuit of drug development processes that value the voice of children and youth.